The Status of Women in Khaled Hosseini’s A Thousand Splendid Suns (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Since the time immemorial, women have been treated as less than equal to men in the society, and with the passage of time, this attitude has gone so much deep down into the psyche of women that they used to consider it a usual social norm. Toril Moi uses the terms—‘feminist’, ‘female’ and ‘feminine’ in order to explain this conditioning of women. She explains the first term as political position and the second term as a result of biology but the third is designed by the society. Women have been treated as weak and inferior throughout the world but the situation of women in war-stricken country like Afghanistan under the dark shadow of Mujahideen or Taliban has been very miserable, and still is in the interior of the country where they have no right to get the education or to go outside for work and so on and so forth. Khaled Hosseini in A Thousand Splendid Suns through the characters of two unfortunate women—Mariam and Laila, tries to expose the functioning of male dominated society and the struggle of women for their existence. Thus, the present research paper intends to explore the status of women and their struggle for survival in the present novel.